IMPLEMENTATION OF GOOD GOVERNANCE PRINCIPLES IN THE PERFORMANCE OF EAST JAVA PROVINCIAL DEVELOPMENT PLANNING AGENCY EMPLOYEES - Amalia Indah Widuri; Sri Umiyati; Elly Setio Wahyuni (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the performance of employees at the Bappeda Provinsi Jawa Timur from a good governance perspective, referring to Mangkunegara’s performance dimensions. The research employs a descriptive qualitative approach through in-depth interviews, observation, and document analysis involving seven key informants. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, along with source and technique triangulation to ensure data credibility. The findings indicate that institutionally, employee performance is categorized as good, as reflected in high performance indicator achievements, strong implementation of SAKIP (Government Agency Performance Accountability System), and the application of Employee Performance Targets (SKP) and the merit system. The principles of accountability and transparency have been procedurally implemented through reporting mechanisms, public consultation forums, and the publication of performance documents. Organizational effectiveness is demonstrated by program target achievements exceeding established standards, as well as cross-sector coordination in the preparation of strategic planning documents. However, the study also identifies a gap between administrative achievements and the substantive quality of work processes. The challenges include suboptimal inter-departmental data integration, unequal workload distribution, competency mismatches in certain positions, and cross-sector coordination dynamics. These conditions indicate the potential for pseudo-performance, where performance appears formally strong but is not yet fully integrated substantively.